STATE DEBT OF UKRAINE AND OTHER COUNTRIES: A COMPARATIVE ASPECT - PIHNYAK, Tetiana; SLOBODYAN, Maxym; MOVCHAN, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article analyzes research on national debt, which is one of the major economic problems not only in Ukraine but also in the world economy as a whole. The national debt is defined as the total government debt, which is the total amount of borrowed and unpaid debts incurred as a result of government borrowing. It is noted that the increase in the national debt is the result of various factors that force the state to finance itself, especially through government credit. The structure of national debt is analyzed in detail and concepts such as domestic and external debt are explained. A comparative overview of these components in developed and developing countries is provided and the predominance of external debt in Ukraine is emphasized. Official data on the volume and dynamics of the national debt of Ukraine are presented, noting that this indicator has increased significantly over time, with a particularly sharp increase in 2023. A comparative analysis of the national debt of Ukraine with other countries is presented and it is shown that it is moderate in comparison with economically developed countries. It is noted that the increase in national debt in most countries can be caused by various factors, ranging from coronavirus pandemics to political conflicts and other domestic issues. The concept of sovereign credit and its impact on the formation of national debt is examined. The relationship between national debt and budget deficits is examined. The view is expressed that the national debt can be positive or negative depending on the economic direction and policies of the state. It is emphasized that research on national debt is important for understanding the impact of national debt on the economic development of a country.